PENGARUH POTENSI DIRI, ORIENTASI MASA DEPAN DAN LINGKUNGAN KELUARGA TERHADAP PENGAMBILAN KEPUTUSAN SAAT MELANJUTKAN STUDI DI JURUSAN PENDIDIKAN EKONOMI UNIVERSITAS SILIWANGI (Survey pada Mahasiswa Jurusan Pendidikan Ekonomi Universitas Siliwangi Angkat - Herna Herlina; Iis Aisyah; Ati Sadiah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The problem in this research can be seen from the results of initial observations that the economics education major is not the main choice in choosing studies, meaning that students have low interest in entering the economics education major. It is possible that in the future it could lead to a lack of concentration during learning and feeling unsuitable or choosing the wrong major so that the student decides to leave. This research aims to determine the influence of personal potential, future orientation and family environment on decision making when continuing studies at the Department of Economic Education, Siliwangi University. The method used is a survey. Meanwhile, the population was students from the Economics Education Department at Siliwangi University using a proportional random sampling technique with a sample size of 107 respondents. Based on the research results, it is clear that 1) There is a positive and significant influence of personal potential on decision making when continuing studies at the Department of Economic Education, Siliwangi University 2) There is a positive and significant influence of future orientation on decision making when continuing studies at the Department of Economic Education, Siliwangi University 3) There is a positive and significant influence of the family environment on decision making when continuing studies at the Department of Economic Education, Siliwangi University. 4) There is a positive and significant influence of personal potential, future orientation and family environment on decision making when continuing studies at the Department of Economic Education, Siliwangi University.